Study on Surface Hardness and Microstructure of Pure Copper Chip Strips Prepared by LSEM - Yunyun Pi; Xiaolong Yin; Wenjun Deng; Wei Xia (Advances in Materials Science and Engineering)
Large strain extrusion machining (LSEM) is one of the severe plastic deformation (SPD) methods that can improve the mechanical properties of materials. The purpose of this experiment is to study the surface hardness and microstructure of the pure copper chip strips. It was found that most of the grains of the chip strips had been refined to the ultrafine grain grade. Finite element analysis (FEA) simulations were conducted to predict the von Mises equivalent strains. Based on the analysis of variance (ANOVA), further study indicated that the surface hardness of the chip strips was decided by several key parameters including the chip thickness compression ratio, rake angle, and uncut chip thickness during LSEM. Through this analysis, a set of parameters which have the greatest impact on the properties of the material can be found. This set of parameters helps us to achieve the strip with the best performance.